2007
DOI: 10.1097/nen.0b013e31802d6da9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nrf2 in Neurodegenerative Diseases

Abstract: In response to oxidative stress, the nuclear factor E2-related factor 2 (Nrf2) transcription factor translocates from the cytoplasm into the nucleus and transactivates expression of genes with antioxidant activity. Despite this cellular mechanism, oxidative damage is abundant in Alzheimer and Parkinson disease (AD and PD). To investigate mechanisms by which Nrf2 activity may be aberrant or insufficient in neurodegenerative conditions, we assessed Nrf2 localization in affected brain regions of AD, Lewy body var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
477
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(520 citation statements)
references
References 53 publications
(89 reference statements)
23
477
1
2
Order By: Relevance
“…Activation of the Nrf2-ARE system in PD has been demonstrated by the upregulation of nigra immunoreactivity for regulated proteins, including NOQ1 and HO-1 (Riedl et al 1999). Other studies found the localisation of Nrf2 in the SN of PD brain in addition to cytoplasm, observed in neurons (Ramsey et al 2007). Collectively, the data suggest that the Nrf2-ARE signal has been activated in PD, which will counteract Nrf2-activated gene transcription.…”
Section: Parkinson's Diseasementioning
confidence: 86%
See 2 more Smart Citations
“…Activation of the Nrf2-ARE system in PD has been demonstrated by the upregulation of nigra immunoreactivity for regulated proteins, including NOQ1 and HO-1 (Riedl et al 1999). Other studies found the localisation of Nrf2 in the SN of PD brain in addition to cytoplasm, observed in neurons (Ramsey et al 2007). Collectively, the data suggest that the Nrf2-ARE signal has been activated in PD, which will counteract Nrf2-activated gene transcription.…”
Section: Parkinson's Diseasementioning
confidence: 86%
“…In the AD brain, Nrf2 predominantly localises in the cytoplasm of hippocampal neurons and not a component of Aβ plaques or NFTs. Immunoblotting studies suggested that the Nrf2 levels were reduced in AD cases (Ramsey et al 2007). Another study has shown that the expression of astroglial HO-1 is elevated in the temporal and hippocampus in mild cognitive impairment in AD as compared with controls (Schipper et al 2006).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…p62/SQSTM1 aids in clearing dysfunctional mitochondria tagged for degradation by the Pink1-Parkin system, two genes involved in familial PD (see above and (Narendra et al 2010a;Geisler et al 2010a)). Loss of p62/SQSTM also correlates with reduced activity of NFE2L2 in neurons and astrocytes affected by neurodegenerative diseases (Du et al 2009a;Ramsey et al 2007). Interestingly, a lower incidence of PD can be found in individuals carrying a Nfe2l2 haplotype that correlates with increased transcriptional activity (von Otter et al 2010), and expression of NFE2L2 in a Drosophila melanogaster model of PD is protective against neurodegeneration (Barone et al 2011).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 97%
“…Hence, pharmacological induction of HO-1 via Nrf2 pathway might be an important strategy in modulating neuroinflammation. Considering the protective effects of Nrf2 against oxidative injury, recent studies have also implicated Nrf2 in neuroprotection [17,18].Artemether (Figure 1) is the lipid-soluble derivative of artemisinin [19]. Although currently used in the treatment of malaria, experiments on experimental rheumatoid arthritis have shown that artemether could be offered as a second-line drug treatment of rheumatoid arthritis [20].…”
mentioning
confidence: 99%